Championing innovation in the global corporation - Shane, Scott
Managers in different countries clearly prefer different approaches to championing; a study offers guidelines for making the choice.
Rapid technological and organizational change, coupled with the globalization of business, has led to a need for managers to understand how to champion innovation in different cultures. As the championing styles managers prefer vary greatly across countries, the amount of adaptation managers need to make in the championing styles can vary from very little to a great deal, depending on where they are from and where they are trying to champion innovation. Cultural differences explain patterns of similarity and difference in championing styles across countries. However, culturally appropriate championing styles are not always the ones that promote the most innovation. Consequently, managers face an important strategic decision : Do they change their own culture to encourage acceptance of effective championing styles, or do they select locations for innovation in which the culture is most accepting of effective championing styles?
Scott Shane explains how to gain support for innovation by identifying the culturally appropriate championing style.
Keywords: Innovation; Global corporation